An African swine fever update for food scientists - Krueger, Erika Leigh (My University, 2025)
African swine fever virus (ASFV) is a highly contagious pathogen that causes African swine fever (ASF) disease in both wild and domestic swine, with mortality rates up to 100%. The potential for this virus to have a significant economic impact on the pork industry classifies it as a high-consequence pathogen. The global food system has become increasingly interconnected. ASFV poses a risk not just to the pork supply but to other market sectors that rely on byproducts from swine production or that provide goods and services to both the animal agriculture and food processing industries. Effective monitoring and surveillance activities are critical in preventing ASF in regions free from the virus. Implementation of multiple mitigation strategies can facilitate a swift and effective response to ASF if it occurs, to limit damage. This report examines the existing literature regarding ASF and its impact on the food system. First, a profile of the virus, clinical disease presentations, and a brief history of outbreaks will provide background on the overall issue. A further examination of transmission routes reveals potential ways to employ both proactive and reactive mitigation strategies to combat the risk of the disease to the global food system. As with any disease-causing pathogen, diagnostics are a critical piece of preventing and/or responding to a potential ASF outbreak and must be developed proactively so that an adequate response plan can be executed. Many aspects of diagnosis make testing for ASF complex, and mitigation strategies may not be effective when employed in different contexts. Finally, an assessment of the current knowledge gaps can be utilized to inform not only future research but also to improve the existing mitigation frameworks for ASF and other pathogens that may pose a risk to the global food system.
Keywords: Animal disease; Swine; Food science